The Effect of Hypoxic Mesenchymal Cell Secretome Administration on VEGF Levels In Type 1 Diabetes Rats Model - Jumena, Finanda; Amalina, Nur Dina; Dewi Antari, Arini (International Journal of Cell and Biomedical Science, 2022)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterised by the cessation of insulin production due to pancreatic β-cell damage resulting in an increase in blood glucose. This study aims to analyse the effect of hypoxic secretome MSCs on the angiogenesis process through the observation of VEGF levels in T1DM rats model. The twenty animal model were randomly assigned to four groups: control T1DM, T1DM with HS-MSCs 0.5 mL intraperitoneal treatment (T1), and TIDM with hypoxic secretom mesenchymal stem cells (HS-MSCs) 1 mL intraperitoneal treatment (T2). The T1DM rats model was induced by a single intraperitoneal (IP) injection of freshly prepared streptozotocin (STZ) at a dose of 65 mg/kg of body weight. The VEGF levels was analyses under ELISA assay. The results showed that VEGF levels of T1 (68.86±4.78) and T2 (53.83±10.86) groups were significantly upregulated in treatment of HS-MSCs. Taken together, HS-MSCs potentially reduce glucose levels on T1DM through VEGF up-regulation.